The physiological dissimilarities of Holstein dairy cows with different milk yields. Issue 1 (17th October 2022) - Dong, Jianan; Liu, Yongjun; Li, Songze; Sun, Zhe; Chen, Xue; Wang, Duojia; Qin, Guixin; Zhang, Xuefeng; Aschalew, Natnael Demelash; Wang, Tao; Zhen, Yuguo
Abstract: Background: Even if breed, parity, dietary and environmental management are same, dairy cows still have notable differences in milk yield that may be underpinned by physiologic differences. Objectives: This study aimed to investigate the physiological dissimilarities of dairy cows with different milk yields. Methods: Thirty cows were sorted into high milk‐yielding cows (group H: 58.93±2.31 kg/day), moderate milk‐yielding cows (group M: 44.99±0.54 kg/day), and low milk‐yielding cows (group L: 24.99±6.83 kg/day) according to milk yield. Blood was collected and serum parameters were assessed. Rumen fluid was collected for the evaluation of rumen fermentation parameters (RFPs) and bacterial community composition (BCC). Results: Serum prolactin, growth hormone, glutathione peroxidase, immunoglobulin A and non‐esterified fatty acid had a significantly positive correlation with milk yield ( p < 0.05), whereas serum glucagon and total antioxidant capacity had a significantly negative correlation with milk yield ( p < 0.05). The concentration of valeric acid and the ratio of acetic acid to propionic acid in the rumen fluid in group H was significantly lower than that in group L ( p < 0.05). The concentration of acetic acid and butyric acid in group H was significantly lower than that in groups M and L ( p < 0.05). The relative abundances of Ruminococcaceae_NK4A214 _group, Prevotella_1, Rikenellaceae_RC9_gut_group, Christensenellaceae_R‐7_group, Muribaculaceae, and Ruminococcus_2 were negatively correlated with milk yield, whereas the relative abundance of Succinivibrionaceae_UCG‐001, Lachnospiraceae_NK3A20_group, Shuttleworthia and Dialister were positively correlated with milk yield ( p < 0.05). Conclusions: This study indicates that dairy cows with different milk yields have clear divergence in serum indicators, RFPs, BCC and rumen microbial metabolism. Abstract : Under the same management and feeding conditions, dairy cows had large differences in milk yield. The physiological dissimilarities of dairy cows with different milk yields were investigated in this study. Results indicated that dairy cows with different milk yields have obvious divergence in hormones, oxidative stress status, immunoglobulin levels, rumen fermentation parameters, bacterial community composition and rumen microbial metabolism.